Pengaruh Pemberian Jus Lidah Buaya (Aloe vera) terhadap Berat Potong, Berat Karkas, Non Karkas dan Lemak Abdominal Ayam Broiler - Wilhelmus Subani (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
This study aimed to study the effect of aloe Vera juice on slaughter weight, carcass, and belly fat of broiler chickens. This research was conducted at the poultry farm belonging to the Faculty of Agriculture Animal Husbandry Study Program. This study uses an experimental method with a Completely Randomized Design (CRD) consisting of 4 units and 4 units consisting of 16 experimental units and each experimental unit consisted of 5 broilers. The treatment given was P0: 100% drinking water, P1: 95% drinking water + 5% aloe vera juice, P2: 90% drinking water + 10% aloe vera juice, P3: 85 % drinking water + 15% aloe vera juice. Variables that are difficult to cut weight, carcass weight, non carcass weight, and stomach weight of broiler chickens. Analysis of variance showed that that giving aloe vera juice as a feed additive has a significant effect (P <0.05) to the percentage of carcass weight, cut weight, weight and percentage of stomach fat in broiler chickens, but not ideal for carcass weight in broiler chickens. Besides that, giving 10% aloe vera juice in drinking water as a food additive gives the best results on the performance of broiler chickens.